Diversity of Plant Species in Homestead Area of Moulvibazar District in Bangladesh (SAARC Journal of Agriculture, 2022)
The study was conducted at Kamalganj Upazila of Moulvibazar district in Bangladesh during January to September 2015 to observe the diversity of plant species in the homestead area with their arrangement and to explore the relationships of plant diversity with the selected characteristics of the respondents. Face to face interview was performed with 135 respondents with the help of questionnaire. A total of 92 plant species, 45 vegetables species were recorded in the homestead of the study area. Out of different categories of plant species, 35 timber, 36 fruits and 21 medicinal and other plants were recorded. Most of fruit plants and medicinal and other plant species were found in front yard and backyard of homestead area. Timber trees were dominated at boundary side than any other side of homesteads. Diversity of fruit (0.79-0.99), timber (0.77-0.93) and medicinal plant species (0.77-0.96) were high in most of the unions. Mango Jackfruit, Papaya, Coconut were dominant fruit species. Acasia hybrid and Mehogony were dominant timber species. Coriander (Coriandrum sativum), Areca nut (Areca catechu), Tulsi (Ocimum americanum), Neem (Azadirachta indica), Bamboo (Bambusa sp), Pudina (Mentha spicata) and Bohera (Terminalia bellerica), were dominant medicinal and other plant species. There was a positive correlation between plant diversity with most of the selected characteristics of the respondents. Results conclude that plant diversity in homestead areas of Kamalganj upazila could be a good option for improving the livelihood of the respondents.SAARC J. Agric., 19(2): 285-299 (2021)